Plasma Soluble CD14 Subtype Levels Are Associated With Clinical Outcomes in Critically Ill Subjects With Coronavirus Disease 2019. (9th December 2021) - Mabrey, F. Linzee; Morrell, Eric D.; Bhatraju, Pavan K.; Sathe, Neha A.; Sakr, Sana S.; Sahi, Sharon K.; West, T. Eoin; Mikacenic, Carmen; Wurfel, Mark M.
Abstract : Supplemental Digital Content is available in the text. Abstract : IMPORTANCE: In bacterial sepsis, CD14 and its N-terminal fragment (soluble CD14 subtype, "Presepsin") have been characterized as markers of innate immune responses and emerging evidence has linked both to coronavirus disease 2019 pathophysiology. OBJECTIVES: Our aim was to determine the relationship between the soluble form of CD14 and soluble CD14 subtype plasma levels, coronavirus disease 2019 status, and coronavirus disease 2019-related outcomes. DESIGN: A prospective cohort study. SETTING: ICUs in three tertiary hospitals in Seattle, WA. PARTICIPANTS: Two-hundred four critically ill patients under investigation for coronavirus disease 2019. MAIN OUTCOMES AND MEASURES: We measured plasma soluble CD14 and soluble CD14 subtype levels in samples collected upon admission. We tested for associations between biomarker levels and coronavirus disease 2019 status. We stratified by coronavirus disease 2019 status and tested for associations between biomarker levels and outcomes. RESULTS: Among 204 patients, 102 patients had coronavirus disease 2019 and 102 patients did not. In both groups, the most common ICU admission diagnosis was respiratory failure or pneumonia and proportions receiving respiratory support at admission were similar. In regression analyses adjusting for age, sex, race/ethnicity, steroid therapy, comorbidities, and severity of illness, soluble CD14 subtype was 54% lower in coronavirus disease 2019 than noncoronavirus disease 2019 patients (fold difference, 0.46; 95% CI, 0.28–0.77; p = 0.003). In contrast to soluble CD14 subtype, soluble CD14 levels did not differ between coronavirus disease 2019 and noncoronavirus disease 2019 patients. In both coronavirus disease 2019 and noncoronavirus disease 2019, in analyses adjusting for age, sex, race/ethnicity, steroid therapy, and comorbidities, higher soluble CD14 subtype levels were associated with death (coronavirus disease 2019: adjusted relative risk, 1.21; 95% CI, 1.06–1.39; p = 0.006 and noncoronavirus disease 2019: adjusted relative risk, 1.19; 95% CI, 1.03–1.38; p = 0.017), shock, and fewer ventilator-free days. In coronavirus disease 2019 only, an increase in soluble CD14 subtype was associated with severe acute kidney injury (adjusted relative risk, 1.23; 95% CI, 1.05–1.44; p = 0.013). CONCLUSIONS: Higher plasma soluble CD14 subtype is associated with worse clinical outcomes in critically ill patients irrespective of coronavirus disease 2019 status though soluble CD14 subtype levels were lower in coronavirus disease 2019 patients than noncoronavirus disease 2019 patients. Soluble CD14 subtype levels may have prognostic utility in coronavirus disease 2019.